Media Pembelajaran Interaktif Fabrikasi PCB Berbasis Augmented Reality - Fhadel Wedi Pratama; Fitri Nova Nova; Deddy Prayama; Taufik Gusman (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
Augmented Reality (AR), is a technology with the concept of combining the dimensions of the real world with the dimensions of the virtual world that is displayed in real time. This is done by displaying a 3D object on a predetermined marker, which is a special pattern that is unique and can be recognized by the application. Smartphones allow the development of Augmented Reality applications cheaply and can be accessed by many users. Augmented Reality can be used in various fields, one of which is a learning media to learn how to do manual PCB fabrication, so that it can be used as a new interactive learning medium and is expected to stimulate interest from many people to learn by utilizing a smartphone combined with Augmented Reality, in addition to technology that continues to develop at this time with many new features in it, the learning method must also develop along with the advancement of current technological developments. In the results of the research that has been done that the results of the application of Augmented Reality AR) have been successfully implemented on Android-based smartphones by applying the PCB manual fabrication work steps that are displayed when the smartphone with the Android operating system triggers the target marker that has been created